Reflections on diaspora and soft power: community building among female US expats in Southern Europe. Issue 6 (2nd November 2018) - Isaakyan, Irina; Triandafyllidou, Anna
ABSTRACT: Illuminated by life stories of American women in Italy and Greece, our work examines a complex relationship between expatriate collectivity and soft power agency. The data were collected from in-depth interviews with 60 US nationals who live in Italy and Greece. Our findings show that these women shape as a strong diasporic collectivity through activities of ecological civic engagement, which, however, do not result in a successful exercise of soft power. The isolationist nature of their collectivity causes a number of diasporic mistakes and turns their chosen community project into a weak resource for soft power, a translation of which remains highly problematic. The basic mistakes that such expats make while exercising soft power are misunderstanding of the notions of community and its main building tool (civic engagement) as well as overall inability to learn the new culture quickly.